THE LANGUAGE OF INCLUSION: CODE-SWITCHING IN POLITICAL CAMPAIGNS - Xushvaqtova Mohira (TADQIQOTLAR, 2025)
Annotation. This article examines the role of code-switching in political campaigns through a linguistic and sociolinguistic lens. Politicians who aim to connect with multilingual and multicultural audiences often alternate between languages during their speeches. This research identifies the rhetorical and symbolic functions of such switches and emphasizes how they contribute to the creation of inclusive political discourse. The methodology consists of a qualitative discourse analysis of speeches that were delivered by multilingual politicians. The findings indicate that code- switching functions as a tool for audience alignment, identity representation, and emotional emphasis. The study concludes that when code-switching is used authentically, it strengthens political engagement and fosters inclusivity among linguistically diverse voters.